Manajemen Perpustakaan dalam Meningkatkan Literasi Mahasiswa - Baihaqi, Moh. Hamdan; Miftahuddin; Rivan, M.; Naqie, Syah Rizal (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
This study aims to determine the role of libraries, namely librarians, collections, management and increase the interest in reading students and female students of the Islamic University Tribakti Lirboyo Kediri. This research is aims to determine and describe the planning, procurement, use, inventory, inhibiting factors and supporting the library at the Islamic University tribakti. This study is a qualitative research using descriptive methods. Data collection was conducted by interviews, observations, and documentation studies. Data analysis techniques are carried out through descriptive interpretation, data validity test, participation extension, and auditing. Library planning is carried out by musyarawah, organizing is done by election and mutually agreed, implementation is carried out in accordance with the plan and according to their respective duties and supervision is carried out every day such as supervision of circulation and cleanliness, neatness and discipline services. The development of the collection is done by deliberation and submission from the user, the supporting factor is adequate facilities, the inhibiting factor is that the librarians available are not graduates from their fields.